Individual variation in thermally induced plasticity of metabolic rates: ecological and evolutionary implications for a warming world - Gvoždík, Lumír (Philosophical transactions of the Royal Society of London. Series B, Biological sciences, 2024)
Energy metabolism is a fundamental property of life providing the energy for all processes and functions within an organism. As it is temperature-dependent, it mediates the effects of changing climate on ectotherm fitness and population dynamics. Though resting metabolic rate is a highly labile trait, part of its variation is individually consistent. Recent findings show that resting metabolic rate contains consistent variation not only in the elevations (intercepts) but also in the slopes of individual thermal dependence curves, challenging the thermal dependence assumption for this trait in several ectotherm taxa. I argue that among-individual variation in thermal metabolic curves represents a previously undetected component of ectotherm response to climate change, potentially affecting their adaptive capacity and population resilience under increasing stochasticity of thermal environment. Future studies need to examine not only the amount of among-individual variation in thermal metabolic curves across phylogenetic contexts but also other aspects concerning its mechanisms and adaptive significance to improve predictions about the impact of climate change on ectotherm population dynamics. This article is part of the theme issue 'The evolutionary significance of variation in metabolic rates'.
Keywords: energy metabolism; energetický metabolismus; Phylogeny; adaptive capacity; population resilience; Climate Change; repeatability; biologická evoluce; cvičení; Biological Evolution; fylogeneze; Exercise; climate change biology; Energy Metabolism; klimatické změny; thermal performance curves